The proteomic analysis of human neonatal umbilical cord serum by mass spectrometry - Song Hong-juan; Zhang Ping; Guo Xue-jiang; Liao Lian-ming; Zhou Zuo-min; Sha Jia-hao; Cui Yu-gui; Ji Hui; Liu Jia-yin (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the proteome composition and function of human neonatal arterial umbilical cord. Methods: Serum proteomic analyses were performed on samples from both males and females by using a combination of techniques: (1) removal of six high-abundance proteins, (2) tryptic digestion of low-abundance proteins, (3) separation of peptide mixtures by reverse-phase high-performance liquid chromatography (RP-HPLC), and (4) peptide identification using electrospray ionization tandem mass spectrometry (ESI-MS/MS). Results: A total of 837 non-redundant proteins were identified, with 213 male-specific and 239 female-specific proteins. Among them, 319 proteins were identified by at least 2 distinct peptides. The subcellular localization, function, and pathway involvement for each of the identified proteins were analyzed. A comparison of this neonatal proteome to that of adult serum proteome revealed novel biomarkers, such as alpha-fetoprotein and periostin that were specific to newborn infants. Conclusion: These data will contribute to a better understanding of the composition of umbilical cord serum and aid the discovery of novel biomarkers for the prenatal diagnosis of fetal abnormalities.